Carcass characteristics of purebred and crossbred Nellore females fed solely pasture - Pivaro, Thiago Martins; Henrique, Wignez; De Oliveira, Emanuel Almeida [UNESP]; Filho, José Luiz Viana Coutinho; Peres, Roberto Molinari; Carvalho, Victor Galli (Universidade Estadual de Londrina, 2016)
This research aimed to compare carcasses of purebred and crossbred Nellore females reared uniquely on pasture (Brachiaria decumbens and Brachiaria brizantha cv. Marandu). Breeds assessed consisted of purebred Nellore (16) and Nellore x Santa Gertrudis crossbred (16), being 32 ± 1.5 months old. All animals were slaughtered as they reached 450 kg. Crossbred females showed higher slaughter, hot and cold carcass weights and longer lengths (P < 0.05). Conversely, purebred animals attained greater carcass yields (P < 0.05). Nonetheless, crossbred females had higher primal cut weights and plate/ flank percentage (P < 0.05). Also, non-carcass components as kidneys, liver, kidney-pelvic-heart fat showed higher weights for crossbred females (P < 0.05). Thus, regarding beef cattle reared and finished exclusively on grazing areas, crossbred females (Nellore x Santa Gertrudis) may be the most profitable ones for cattle raisers, since they produce heavier slaughtering carcasses. Notwithstanding, they might be interesting for meat industry, for yielding more in prime cuts than purebreds, even if raised at the same conditions and slaughtered at same age.
Keywords: Bovines; Brachiaria; Breeds; Commercial cuts; Slaughter